Pelatihan Pembuatan Database Geologi Melalui Aplikasi Surpac Bagi Siswa Jurusan Geologi Pertambangan SMK Penerbangan Techno Terapan Makassar - Nur, Irzal -; Ramli, Muhammad; Anas, Aryanti Virtanti; Sutardjo Tui, Rini Novrianti; Amalia, Rizki; A, M. Fadhil Fajar; Lasefeati, M. Alfian (Faculty of Engineering UNHAS, 2023)
The creation of a geological database is the initial stage in the mineral estimation process. In this stage, the management and verification of exploration data in the form of borehole data is carried out using a software, one of which is Surpac. Surpac is quite flexible and efficient in meeting the needs of each commodity and mining method. One of the Vocational High Schools that teaches Mining Geology expertise is SMK Penerbangan Techno Terapan Makassar. The curriculum structure of this field consists of general subject groups and vocational subject groups. According to the Regulation of the Director General of Primary and Secondary Education of the Ministry of Education and Culture Number: 07/D.D5/Kk/2018 concerning the Curriculum Structure of Vocational High Schools (SMK)/Madrasah Aliyah Kejuruan (MAK), exploration techniques and mining techniques have the largest proportion in the curriculum structure. This competency requires students to know the characteristics and types of data in exploration activities and the use of technology such as computer programs. Limited access to Surpac software for geological database creation by students of SMK Penerbangan Techno Terapan Makassar causes a lack of knowledge in creating geological databases using Surpac software. The importance of creating a geological database for students of SMK Penerbangan Techno Terapan Makassar is used as a basis by the Department of Mining Engineering through the Laboratory Based Education (LBE) Collaboration program to conduct training on creating a geological database using Geovia Surpac software. The targeted aspect of the training is to increase students' knowledge about the importance of creating a database before estimating as well as introducing the Surpac application. In addition to achieving the target, the service team will later conduct lecture-based training directly to practice the geological database creation tutorial. This training activity also contains the delivery of initial material as well as giving pretests and posttests to measure the extent of students' understanding of database creation and also the Surpac application. The conclusion of this service is that the service carried out can be said to be successful because the results of the pretest and posttest conducted have significant differences where after being given material and also making tutorials, students understand more about the material and also the creation of the database both in terms of quality and quantity of the number of students who answer posttest questions. Based on this, it is recommended to make further training related to software that is often used in the mining world so that it can be a provision for students to enter the world of work.